Religious Protection of Children in Polygamic Families in Langkat Regency Based on Law Number 35 of 2014 Concerning Child Protection - Titi Susanti; Ramadhan Syahmedi; Hafsah Hafsah (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
There are the forms of attention to children's religious values that cannot be implemented properly in polygamous families in Langkat Regency. Responding to the polygamy cases in Langkat Regency, this is an interesting phenomenon to study regarding the protection of the child's religion in the family. This study was field research, with its approach normative. religious protection for children based on Law number 35 of 2014 in several articles, namely articles 6, 25, 26, 39 and 43. The impact on child victims of polygamy who do not receive religious protection in Langkat Regency is that the child is psychologically disturbed. Never again did he hear calls or invitations to pray in congregation, recite the Koran or the advice he had received from his parents. Plus, friends who lack good morals. So that children often find their solutions to all the problems they face. Children become misdirected due to promiscuity and experience depression, so few are trapped in the diseased environment of society. So that children often find their solutions to all the problems they face. Children become misdirected due to promiscuity and experience depression, so few are trapped in the diseased environment of society. However, not all children who are victims of polygamy at this level become wrong associations. There are also those whose personality is getting better. Because attention from his father is still given, although not like before, his mother at home is also protective of his association. The surrounding community and religious leaders also play a role in embracing him so that he remains in an association that brings terdapat bentuk-bentuk perhatian terhadap nilai-nilai agama anak yang belum dapat dilaksanakan dengan baik pada keluarga poligami di Kabupaten Langkat. Menanggapi kasus poligami di Kabupaten Langkat, hal ini menjadi fenomena yang menarik untuk dikaji terkait perlindungan agama anak dalam keluarga. Penelitian ini merupakan penelitian lapangan dengan pendekatan normatif. perlindungan agama bagi anak berdasarkan Undang-Undang nomor 35 Tahun 2014 pada beberapa pasal yaitu pasal 6, 25, 26, 39 dan 43. Dampak terhadap anak korban poligami yang tidak mendapatkan perlindungan agama di Kabupaten Langkat adalah anak terganggu secara psikologis . Tidak pernah lagi dia mendengar panggilan atau ajakan untuk sholat berjamaah, mengaji atau nasehat yang dia terima dari orang tuanya. Ditambah lagi teman-teman yang akhlaknya kurang baik. Sehingga anak sering menemukan solusinya atas segala permasalahan yang dihadapinya. Anak-anak menjadi salah arah akibat pergaulan bebas dan mengalami depresi, sehingga sedikit yang terjebak dalam lingkungan masyarakat yang sakit. Sehingga anak sering menemukan solusinya atas segala permasalahan yang dihadapinya. Anak-anak menjadi salah arah akibat pergaulan bebas dan mengalami depresi, sehingga sedikit yang terjebak dalam lingkungan masyarakat yang sakit. Namun tidak semua anak yang menjadi korban poligami pada tataran ini menjadi pergaulan yang salah. Ada juga yang kepribadiannya semakin membaik. Karena perhatian dari ayahnya tetap diberikan, meski tidak seperti dulu, ibunya di rumah juga protektif terhadap pergaulannya. Masyarakat sekitar dan tokoh agama juga berperan untuk merangkulnya agar tetap dalam pergaulan yang membawa kemaslahatan